A Two-Stage Distributed Architecture for Voltage Control in Power Distribution Systems - Robbins, Brett A.; Hadjicostis, Christoforos N.; Dominguez-Garcia, Alejandro D. (IEEE transactions on power systems, 2013)
In this paper, we propose an architecture for voltage regulation in distribution networks that relies on controlling reactive power injections provided by distributed energy resources (DERs). A local controller on each bus of the network monitors the bus voltage and, whenever there is a voltage violation, it uses locally available information to estimate the amount of reactive power that needs to be injected into the bus in order to correct the violation. If the DERs connected to the bus can collectively provide the reactive power estimated by the local controller, they are instructed to do so. Otherwise, the local controller initiates a request for additional reactive power support from other controllers at neighboring buses through a distributed algorithm that relies on a local exchange of information among neighboring controllers. We show that the proposed architecture helps prevent voltage violations and shapes the voltage profile in radial distribution networks, even in the presence of considerable penetration of variable generation and loads. We present several case studies involving 8-, 13-, and 123-bus distribution systems to illustrate the operation of the architecture.